Integrating partitioned prices via computational estimation. Issue 8 (August 2017) - DelVecchio, Devon; Jones, William J.; Stenstrom, Eric
Abstract: This paper introduces computational estimation to the literature on consumers' numerical cognition. Computational estimation involves simplifying an arithmetic problem via mathematical procedures to produce an approximate answer. Employing calculation knowledge and approximation together, consumers are likely to use computational estimation as it is relatively accurate while saving cognitive effort compared to calculating values. Three studies applied to partitioned prices in the form of a base price and a percentage discount, demonstrate that when faced with this numeric integration task, the strategy consumers undertake is dependent on the characteristics of the numerals with discounts that are round or close to round being associated with greater use of computational estimation. Further, when employing computational estimation, consumers arrive at more accurate, and lower, price estimates in which they place more confidence than when using alternative an integration strategy. As a result, discounts that are near a round value are preferred to those that are not; a result that is dependent upon the use of computational estimation.